Dosimetric comparison of proton radiotherapy plan versus intensity-modulated photon radiotherapy plan for craniospinal irradiation in children with central nervous system tumors - CHEN Qing, SUN Lei, BI Bin, WANG Yuxiang, XU Rui (精准医学杂志)
Objective To investigate the differences in dosimetry between four radiotherapy techniques in craniospinal irradiation (CSI) for central nervous system (CNS) tumors in children. Methods CT images for tumor localization before radiotherapy were collected from 33 children with CNS tumor who underwent CSI passive scattering proton therapy (PSPT) in Zibo Wanjie Tumor Hospital from May 2005 to May 2023, and the radiotherapy target volume and organ at risk (OAR) were contoured. These CT images were used to design and evaluate four treatment plans in the Eclipse proton and Eclipse photon treatment planning systems, i.e., PSPT, intensity-modulated proton therapy (IMPT), photon static intensity-modulated radiotherapy (IMRT), and photon volumetric-modulated arc therapy (VMAT), which were designated as the PSPT, IMPT, IMRT, and VMAT groups, respectively. Related dosimetric parameters were compared between the four plans, including the conformity index (CI), homogeneity index (HI), and gradient index (GI) of the planning target volume (PTV), the dose to 95% of the volume (D95), dose to 5% of the volume (D5), and mean radiation dose (Dmean) for PTV, OAR, and normal tissue (NT), and the percentage of volume receiving different doses (V5, V10, V20). Results Compared with the IMPT and PSPT groups, the IMRT and VMAT groups had significantly higher D95, Dmean, CI, and GI of PTV (F=8.452-22.671,t=-20.352-9.779,P<0.05) and significantly lower D5 and HI of PTV (F=9.782-15.234,t=3.462-9.512,P<0.05). Compared with the IMRT and VMAT groups, the IMPT and PSPT groups had significantly lower Dmean, V5, V10, and V20 of OAR and NT (F=15.189-899.507,H=100.583,483.825,t=-110.622-27.767,P<0.05), and compared with the IMPT group in terms of OAR, the PSPT group had a significantly lower Dmean of the eyeballs, lenses, and thyroid (F=201.163,H=100.583,483.825,t=-21.536-27.767,P<0.05). Conclusion In CSI for pediatric CNS tumors, IMRT and VMAT plans have better PTV conformity and homogeneity than IMPT and PSPT plans, and compared with photon-based intensity-modulated radiotherapy plans (IMRT and VMAT), proton-based radiotherapy plans (IMPT and PSPT) can better protect NT and OAR outside the PTV in pediatric patients.